Avaliação mecânica de alvenarias de vedação armadas nas juntas horizontais submetidas à flexão lateral - Romário de Souza Lima (2022)
ABNT NBR 15575: 2021, entitled as Housing Buildings - Performance - Part 4: Requirements for internal and external vertical fencing systems, is the reference to be followed for companies in the civil construction segment to provide adequate housing buildings to users who meet the minimum desirable requirements and, by extension, are not punished in the event of non-compliance. This research aims to experimentally evaluate the performance of sealing masonry with reinforcements inserted in their horizontal joints. Regarding the sealing system (internal or external), it is known that the reinforcement of armor can provide improvements in terms of structural performance. The present study evaluated the mechanical performance of sealing masonry with thicknesses of 9 and 14 cm. Empirically, the constraints: height ≤ 3.00 m and thickness ≥ 14 cm, started to be used in the market for any masonry with conventional materials to perform satisfactorily. For sealing masonry with a block of 9 cm with joint reinforcement, the performance obtained is not known. Reinforcements in wire trusses can validate them or contribute to the performance criteria in compliance with ABNT NBR 15575: 2021. The experimental evaluation method is applied in the laboratory on full-scale walls with dimensions of 3.00 meters in length by 2.80 meters in height and for each masonry a soft body impact test is carried out. The masonry has a thicknesses of 9 and 14 centimeters, being molded with ceramic sealing blocks with horizontal holes. Non-reinforced masonry, masonry with a flat wire truss galvanized in alternate rows and fully reinforced are evaluated, with at least two masonry being molded for each treatment and a reference masonry (without reinforcement).